GENERASI MUDA SADAR BISING (GEMA DARING) PADA PELAJAR SMA - SMK DI KOTA DENPASAR - Saputra, K.A.D.; Dewantara, I.P.S.; Suardana, W. (Buletin Udayana Mengabdi, 2023)
Objective: To increase knowledge and awareness about the risk of noise-induced hearing loss as a promotive effort in preventing noise-induced hearing loss among high school and vocational high school students in Denpasar City. Methods: Implementation of webinars and online workshops on the introduction and treatment of noise-induced hearing loss in high school and vocational high school students in Denpasar City. The increase in knowledge in this activity is assessed by the results of the pre-test and post-test. Results: A webinar and workshop "Generasi Muda Sadar Bising" has been held on September 25, 2021 using Zoom. This activity was attended by 134 SMA – SMK students from 5 schools in Denpasar. There was an increase in knowledge of the participants of webinars and workshops where the mean value of the pre-test and posttest increased from 66.89 to 77.68. The participants seemed active in the workshop activities and were able to follow the activities from beginning to end. Conclusion: Webinars and workshops about awareness of noises for the young generation can increase the knowledge and awareness of among high school and vocational high school students in Denpasar City. This activity can be an effective promotional effort in preventing noise-induced hearing loss. Keywords: Noise awareness, Udayana’s dedication, Noises Webinar